MUSAD: validation of the music-based scale for autism diagnosis in adults with intellectual disability. Issue 1 (1st June 2016) - Bergmann, Thomas; Heinrich, Manuel; Ziegler, Matthias; Dziobek, Isabel; Diefenbacher, Albert; Sappok, Tanja
Abstract : Background : The MUSAD is a semi-structured approach using a music-based interactional framework to assess autism spectrum disorders (ASD) in adults with intellectual disability (ID). A preliminary study provided first evidence for good feasibility, objectivity, reliability and construct validity. Objective : The ongoing validation (2012–2016) aims to investigate the diagnostic validity of the instrument. Methods : All analyses will be applied to an age-, gender- and IQ-matched clinical sample of more than 100 patients with suspected ASD. A factor analysis will be conducted to confirm the structural model of the MUSAD draft version. Items for an appropriate diagnostic algorithm will be selected based on their clinical utility. A ROC analysis will be applied to assess the ability to discriminate between ASD and non-ASD. Results : Preliminary results gathered in a sample of n  = 88 patients using a diagnostic algorithm based on 14 items showed an appropriate sensitivity/specificity of 82/73%. Final results will be presented at the EMTC. Conclusions : The MUSAD is a valid approach to support clinicians identifying ASD in adults with ID.